Relation of migraine headache with gastro-intestinal disorders - Wahid ul Hassan; Mohan Singh (Indian Journal of Integrative Medicine, 2023)
An observational study was designed to study the relation of migraine headache with gastro-intestinal disorders. 2948 cases of Migraine clinically diagnosed by Ayush doctors working at various Institutions under the purview of Directorate of Ayush, Jammu & Kashmir, India were enrolled in the study. The data of the patients was recorded in Case Record Forms and a questionnaire specially designed for the purpose. The study reveals that the Gastro-intestinal disorders along with co-relation of various Intestinal Gases play a major role in triggering the episodes of migraine attacks.